Assigning Xiuguozhangia (genus incertae sedis) to Pseudoberkleasmiaceae (Dothideomycetes, Pleosporomycetidae, Pleosporales) and introducing X. broussonetiae as a novel species - Deecksha Gomdola; Rajesh Jeewon; Eleni Gentekaki; Ruvishika S. Jayawardena; Kevin D. Hyde; Fatimah Alotibi; Yong Wang (MycoKeys)
Xiuguozhangia species are dematiaceous hyphomycetes that are characterised by acropleurogenous, dictyoseptate, campanulate or cheiroid, and brown to dark brown conidia that are composed of several layers of cells radiating from a protuberant basal cell, and mostly seen with appendages arising from the apical cells. The genus was introduced based on morphology to accommodate five of the six Piricaudiopsis species that exhibited holoblastic conidial ontogeny. Xiuguozhangia was referred to as Ascomycota genus incertae sedis as it was challenging to resolve its taxonomic placement based solely on the available morphological data (no DNA sequence data was previously available). In this study, we provide DNA sequence data for LSU, ITS, SSU, TEF1, and RPB2 for our isolates, collected from Broussonetia papyrifera (Moraceae) in northern Thailand. Based on morphology, we classify our isolates as Xiuguozhangia. Since they form a sister lineage to Pseudoberkleasmium, we place Xiuguozhangia in Pseudoberkleasmiaceae (Pleosporales). Within Xiuguozhangia, we establish these two isolates as a new taxon, Xiuguozhangia broussonetiae, in view of the presence of new conidiogenous cells developing from subtending cells. Xiuguozhangia broussonetiae differs from the extant species in the genus as it has longer conidiophores that are sometimes branched, comprising numerous septa, and its appendages are mostly untapered (sometimes tapering) towards the tips, a feature not observed in other Xiuguozhangia species. This is the first study to provide DNA sequence data and phylogenetic relationships for Xiuguozhangia. Furthermore, we analysed selected DNA sequence data and provided an updated phylogenetic tree incorporating all families (with representative genera) of Pleosporales.